2020
DOI: 10.14574/ojrnhc.v20i2.631
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Depressive Symptoms in Rural Farm Women Aged 50 and Over

Abstract: Purpose: Aspects of farming and farm life can contribute to higher levels of depressive symptoms resulting in an increased risk for injury and development of chronic disease and a decrease in overall quality of life. Rural farm women can be subjected to stressors from farming as an occupation, their role within the agrarian culture, and life in a rural area. The purpose of this study was to examine the associations of demographic characteristics, agricultural occupational factors, and health indicators with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In this study, the stress level was a significant predictor of depressive symptoms. Similar results have been found among other populations (Maideen et al, 2014; Sangon, 2004; Witt et al, 2020). Maideen et al (2014) found that a high perceived stress level predicted increased depression among Malaysian adults.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the stress level was a significant predictor of depressive symptoms. Similar results have been found among other populations (Maideen et al, 2014; Sangon, 2004; Witt et al, 2020). Maideen et al (2014) found that a high perceived stress level predicted increased depression among Malaysian adults.…”
Section: Discussionsupporting
confidence: 91%
“…Maideen et al (2014) found that a high perceived stress level predicted increased depression among Malaysian adults. Witt et al (2020) found that higher levels of perceived stress among female farm workers significantly predicted higher levels of depression, while Sangon (2004) found that Thai women ( n = 142) with a higher perception of stress had the most significant severe depression. Stress in patients on HD could be viewed as the tendency to overreact to situations and intolerance of anything that stops them from succeeding in their goals.…”
Section: Discussionmentioning
confidence: 99%